2010
DOI: 10.1182/blood-2009-07-232330
|View full text |Cite
|
Sign up to set email alerts
|

PI3K p110δ regulates T-cell cytokine production during primary and secondary immune responses in mice and humans

Abstract: We have previously described critical and nonredundant roles for the phosphoinositide 3-kinase p110␦ during the activation and differentiation of naive T cells, and p110␦ inhibitors are currently being developed for clinical use. However, to effectively treat established inflammatory or autoimmune diseases, it is important to be able to inhibit previously activated or memory T cells. In this study, using the isoform-selective inhibitor IC87114, we show that sustained p110␦ activity is required for interferon-␥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
194
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(213 citation statements)
references
References 51 publications
14
194
5
Order By: Relevance
“…Subsequent experiments using TCR transgenic T cells showed that p110␦ plays a more prominent role in clonal expansion of antigen-specific CD4 T cells (38). In addition, the p110␦-selective inhibitor IC87114 was reported to inhibit proliferation of both mouse and human T cells (29). An important caveat is that when present at concentrations above 1 M, IC87114 inhibits proliferation of T cells with inactive p110␦ (29).…”
Section: Pi3kmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent experiments using TCR transgenic T cells showed that p110␦ plays a more prominent role in clonal expansion of antigen-specific CD4 T cells (38). In addition, the p110␦-selective inhibitor IC87114 was reported to inhibit proliferation of both mouse and human T cells (29). An important caveat is that when present at concentrations above 1 M, IC87114 inhibits proliferation of T cells with inactive p110␦ (29).…”
Section: Pi3kmentioning
confidence: 99%
“…In addition, the p110␦-selective inhibitor IC87114 was reported to inhibit proliferation of both mouse and human T cells (29). An important caveat is that when present at concentrations above 1 M, IC87114 inhibits proliferation of T cells with inactive p110␦ (29). Therefore, cellular effects of IC87114 above 1 M might result from achieving a more pan-PI3K inhibition profile.…”
Section: Pi3kmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that PI3Kd activity regulates post-Golgi transport and secretion of TNF in macrophages 18,19 . PI3Kd is similarly implicated in the release of cytokines from other immune cells [20][21][22][23][24] , and PI3Kd-selective inhibitors have significant anti-inflammatory efficacy [24][25][26] . A dual PI3Kg/d inhibitor has been shown to reduce damage in myocardial infarction 27 .…”
mentioning
confidence: 99%